2018
DOI: 10.4103/ija.ija_672_17
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparative study on customised versus fixed sized pillow for tracheal intubation in the sniffing position by Macintosh laryngoscopy

Abstract: Background and Aims:The sniffing position has been most commonly used for positioning of the head and neck to facilitate tracheal intubation. However, the optimum degree of head elevation for the optimal laryngeal view is not well studied, especially in non-Western countries. The present study was aimed to compare the use of a fixed height pillow versus a customised pillow (CP) height for head elevation, in terms of glottis visualisation and time required for tracheal intubation.Methods:With research and ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The positioning cushions were employed and strategically placed under the left shoulder girdle and the left lumbar region to minimize the degree of misalignment. This technique supports studies reported in the past that employed cushions for head positioning to visualize the glottis better [9,10].…”
Section: Discussionsupporting
confidence: 86%
“…The positioning cushions were employed and strategically placed under the left shoulder girdle and the left lumbar region to minimize the degree of misalignment. This technique supports studies reported in the past that employed cushions for head positioning to visualize the glottis better [9,10].…”
Section: Discussionsupporting
confidence: 86%
“…A randomized controlled trial published in 2018 concluded that the EAM and the sternal notch give better glottic visualization and intubating conditions, difficult airway was however excluded from this study as well. 16 There is limited evidence showing that sniffing position which is external auditory meatus and the sternal notch at the same horizontal level and 1.5-inch cushion added to achieve further elevation has an advantage. 17 A comparative study done in 2019 comparing laryngoscopy position attained by 7 cm high pillow and that attained by horizontal alignment of an external auditory meatus-sternal notch(AM-S).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported objective measurements of an anaesthesiologist's posture by measuring various angles of the neck, back, arms and leg joints while performing intubation in the sniffing position. [ 3 ] However, there is a paucity of objective data available on laryngoscopy and tracheal intubations performed with HELP in supine and a 25° backup.…”
Section: Introductionmentioning
confidence: 99%